Pipes or Prisms? Personal Networks, Network Mechanisms, and Formal Support Receipt In The Wake Of Deepwater Horizon Oil Spill. Issue 3 (3rd July 2021) - Puetz, Kyle; Mayer, Brian
ABSTRACT: Social networks are commonly discussed in reference to processes of disaster recovery but rarely explicitly measured. We employ a mixed-methods approach drawing upon the personal-network data of 265 oyster workers in the wake of the Deepwater Horizon oil spill and qualitative accounts of individual experiences during the recovery process. We find evidence of two potential mechanisms linking network structure with the receipt of formal support: a networks-as-pipes approach linking networks and access to relevant information in the wake of a disaster and a networks-as-prisms approach where networks signal their social identities, shaping post-disaster actions and behaviors.